Working capital investment and firm performance : analysis of financial constraint as moderating role - Jamiu Adeniyi, Akindele; Asri, Marsidi; Shaharudin, Jakpar; Akeem Adekunle, Adeyemi; Lateef, Yunusa (Inderscience Enterprises Ltd., 2024)
This study examines the moderating role of financial constraints on the impact of working capital investment on firms’ performance. The study sample comprises 902 non-financial firms-years registered on the Nigerian Stock Exchange. Using the dynamic panel model over ten years (2009–2018), the empirical evidence indicates a significant impact between the cash conversion cycle, inventory days, and return on assets (nonlinear relationship). Contrarily, account receivable days and account payable days show the absence of a nonlinear relationship. Similarly, financial constraints proxy cash flow has a moderating effect between working capital investment and performance, while the cost of external financing has no moderating effect. It is thus inferred that managers with specialised skills and competency can support the organisation’s working capital strategy and mitigate the asymmetric information and agency costs to reduce the effect of financial constraints, thereby increasing firms’ performance.